Pemetaan Toko Komputer Berbasis Web di Kabupaten Garut - Fitriani, Leni; Agustin, Yoga Handoko; Fauzi, Bayu Muhammad (Jurnal Algoritma, 2023)
A computer shop is a place that sells equipment related to computers. As technology advances, people's needs for computer shop locations are also increasing. Computer shops themselves not only sell various computer needs such as hard disks, Random Access Memory, and accessories such as mice and keyboards, some computer shops also sell products in the form of services such as computer servicing, computer assembly, installing software, and buying and selling used computers. Currently, information about computer shops only consists of explanations about the shop and mapping of computer shop location points, there is no information based on completeness categories in the form of product services, computer accessories, computer buying and selling. This means that the public or potential consumers do not know much about the location and search for computer shops in the city of Garut. Because the level of public need for the availability of goods and services will be very necessary, an application system is needed that can help increase store sales and the needs of the public as consumers. The aim of this research is the design and development of web-based computer shop mapping in Garut Regency. The methodology used to design this application is Rational Unified Process (RUP) with several stages of inception, elaboration, construction, and using Unified Modeling Language (UML) modeling. The results of this research are a geographic information system mapping computer shops to help make it easier for users or potential consumers to choose a complete computer shop and recommended computer shop.